2019
DOI: 10.1177/1747954119884441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute antagonist static stretching on upper-body agonist power

Abstract: There are many studies showing acute static stretching to be detrimental to power generation. However, the majority have focused upon the impact of stretching the agonist musculature. To date, few have examined the potential benefits of acute antagonist static stretching; none have focused on upper-body power. Utilising a repeated-measures design, 30 male participants were randomly assigned to one of two groups whereupon they performed four bench-throw tests; two control (NO-STRETCH) and two experimental (STRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the use of different assessment methods to evaluate strength is an important aspect to consider when investigating the effects on strength gains (10). In addition, recent studies have observed that muscle activation and performance tend to increase subsequently to a stretch applied to antagonist muscles of the tested one (17,57,78); in opposition to what is observed for stretching the agonist muscle (12). It would be interesting if future studies consider exploring RT plus stretch of the antagonist muscle group on muscular adaptations.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the use of different assessment methods to evaluate strength is an important aspect to consider when investigating the effects on strength gains (10). In addition, recent studies have observed that muscle activation and performance tend to increase subsequently to a stretch applied to antagonist muscles of the tested one (17,57,78); in opposition to what is observed for stretching the agonist muscle (12). It would be interesting if future studies consider exploring RT plus stretch of the antagonist muscle group on muscular adaptations.…”
Section: Resultsmentioning
confidence: 99%